A new application of the traditional Fenton process to gold cyanide synthesis using acetonitrile as a cyanide source. Issue 20 (9th February 2016) - Yi, Wuzhong; Yan, Xiaoqing; Li, Renhong; Wang, Jian-Qiang; Zou, Shihui; Xiao, Liping; Kobayashi, Hisayoshi; Fan, Jie
Abstract : We introduced a general Fenton-reaction synthesis of metal cyanide solids using acetonitrile as a green cyanide source. This Fenton-improved cyanation method gets rid of CN − ions and UV-light efficiently, which is green and facile. Abstract : Previous cyanation processes always involved the use of hypertoxic CN − ions or UV-light, which is health-risky and energy-wasting. For the purpose of environment-friendly chemistry, we introduced a general Fenton-reaction synthesis of metal cyanide solids using acetonitrile as a green cyanide source. This Fenton-improved cyanation method gets rid of CN − ions and UV-light efficiently, which is green and facile.